SEDIMENTARY FACIES AND HYDROCARBON RESERVOIR POTENTIAL OF SAND FLAT IN THE UPPER PART OF TAPAK FORMATION IN BANYUMAS AREA, CENTRAL JAVA - Yan Rizal; Wahyu Dwijo Santoso; Alfend Rudyawan; Ricky Adrian Tampubolon; Affan Arif Nurfarhan (Indonesian Institute of Sciences, 2018)
The upper part of Tapak Formation in Kali Cimande consists of alternating sandstones, siltstone and mudstone. The alternating sequence showed a fining and thinning upward bedding pattern. The facies association of the alternation built up by sand flat facies, which characterized by medium sandstone, moderate sorted, with cross-lamination sedimentary structures and mostly on the top of sandstone layer found a bioturbation trace fossils (Skolithos). Mixed flat facies, which is characterized by an alternation of thin layered sandstones with mudstone and siltstone, with lenticular, wavy, and flaser sedimentary structures, contained many forms of bioturbation, such Planolites, Thallasinoides, Lockeia, and Ophiomorpha. Mud flat facies association, is characterized by a repeated of claystone with thin sandstone intercalation, where the ratio of clay content more than 95 % of the total layers, contained abundantly with trace fossil Lockeia. Upper Tapak Formation plays as moderate reservoir potential. The thick sandstone in sand flat facies with moderate to poorly sorted and moderate porosity is required to provide hydrocarbon flows in Banyumas Basin.Bagian atas Formasi Tapak di Kali Cimande terdiri dari perselingan batupasir-batulanau dan mudstone. Sekuen perselingan menunjukkan pola perlapisan menghalus dan menipis ke atas. Asosiasi fasies tersebut terdiri dari fasies sand flat, yang dicirikan oleh batu pasir sedang, pemilahan sedang, struktur sedimen silang-siur serta fosil jejak bioturbasi (Skolithos) pada bagian puncak kebanyakan lapisan batu pasir. Fasies mixed flat, dicirikan oleh perselingan batupasir berlapis tipis dengan mudstone dan batulanau, serta struktur sedimen lentikular, perlapisan bergelombang, dan flaser, mengandung banyak bioturbasi, seperti Planolites, Thallasinoides, Lockeia, serta Ophiomorpha. Asosiasi Fasies sand flat, dicirikan oleh perulangan batulempung dengan sisipan batupasir tipis, dengan kandungan lempung lebih dari 95% total lapisan, serta fosil jejak Lockeia yang melimpah. Formasi Tapak Atas berperan sebagai reservoir potensial sedang. Bagian batupasir tebal di fasies sand flat dengan pemilahan sedang hingga buruk dan porositas sedang diperlukan untuk menyediakan aliran hidrokarbon di Cekungan Banyumas.